Membangun Transportasi Udara Era 5.0 di Indonesia: Perspektif Hukum dan Kebijakan - Lumban Gaol, Selamat; Mardianis, Mardianis; Niru Anita Sinaga; Subhan Zein Sgn; , Budi Prayitno; Anggraeni Rosliana Dewi (UNES Law Review, 2024)
Society 5.0 was initiated by Japan, and inaugurated on January 21, 2019, made as a resolution to the Industrial Revolution 4.0, using modern-based science (Artificial Intelligence, Robots, Internet of Things) for human needs with the aim that humans can live comfortably, including in air transportation, initially focusing on human factors (pilots) began to shift the emphasis to the development of aviation technology. Therefore, it is interesting and necessary to examine how the readiness of laws and policies to build air transportation in the 5.0 era in Indonesia. This research is normative legal research using a statute approach, conceptual approach, and comparative approach and uses secondary data obtained from primary and secondary legal sources related to laws and policies to build air transportation in the 5.0 era in Indonesia. The results show that the existing laws and policies for building air transportation in the 5.0 era in Indonesia are not ready. It is necessary to harmonize and synchronize laws and regulations and policies to build air transportation in the 5.0 era in Indonesia with global regulations and policies in the form of international agreements related to air transportation development in the 5.0 era in the world.